Improving students' creative thinking skills using BBC Microbit in Informatics subjects - Muhammad Syafri Syamsudin; Gunarso; Lala Septem Riza; Suratno (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Information and communication technology (ICT) has become an integral part of modern life and has had a significant impact on the world of education, especially in vocational schools. Education is essentially a process for students to acquire knowledge and develop skills through learning experiences. In this study, the learning method used combines the Science, Technology, Engineering, and Math (STEM) disciplines with a focus on developing computer programs using micro:bit block programming to solve real-life problems. The results of the study show that the use of micro:bit as an alternative teaching method for computer science in vocational schools can improve students' creative thinking skills with an average score of 90 after treatment. This study used a pre-experimental design method with 35 subjects from the X grade of the Computer Network and Telecommunication Engineering program at SMK Negeri 1 Cirebon, using written tests and observations as data collection techniques. The use of simple and inexpensive technology products such as micro:bit can enhance learning effectiveness and help students better understand programming concepts. Therefore, micro:bit can be considered as an alternative teaching method for computer science in vocational schools.